An Exploration of Language Use in the context of CMC - Miller, Jane; Durndell, Alan; Wrennall, Mike; Mayes, Terry (Proceedings of the International Conference on Networked Learning, 2000)
The purpose of this poster is to outline emerging work that is being undertaken at Glasgow Caledonian University to incorporate learning technology into an element of the first-year introduction to psychology module. Currently, for the initial pilot study, computer conferences have been set up for the students and their task is to generate ideas relevant to their essay topics and discuss them online. The students that participate in the online discussion groups are awarded bonus marks for their essays, depending on the extent and quality of their contribution. It is hoped that during the course of the investigation, the study will be repeated a number of times using a different sample of introductory psychology students each semester, with roughly fifty students in each sample. The learning strategy that has been adopted in this investigation is based upon constructivist and socio-cultural learning principles.